The synthesis of oxalate-modiﬁed pyrite/chitosan as an antibacterial composite - Singh, Rashween Kaur Jagjit; Hui, Khee Chung; Nurul Khusna, Mohd Salleh; Peechmani, Prakash; Farhana, Aziz; Hamidah, Abdullah; Ahmad Nazrul, Rosli; Soraya Sambudi, Nonni Soraya (ICE Publishing, 2023)
The combination of organic and inorganic components has produced bioactive materials with excellent properties. Chitosan is a widely used organic component that has received recognition as a biocompatible material. In contrast, naturally occurring pyrite has so far received limited exposure as a biomaterial, despite its great antibacterial activity. Hence, the incorporation of pyrite into the chitosan matrix is expected to highlight the usage of pyrite as a bioactive material, particularly in antibacterial response. In this research, chitosan and oxalate-modified pyrite were combined to form beads at wt% pyrite loadings of 1, 3 and 5%. Energy-dispersive X-ray spectroscopy analysis could confirm the loading of pyrite into the bead matrix. The beads exhibit a high water absorption ability. With the addition of pyrite, the absorption of water could increase up to 37% compared with that of blank chitosan beads. The immersion of beads in simulated body fluid shows the bioactivity of beads by formation of apatite. Microbial activity against Escherichia coli and Staphylococcus aureus is exhibited by all composite beads containing oxalate-modified pyrite, particularly by beads containing 5 wt% oxalate-pyrite.